Literature and History: Study of Nigerian Indigenous Historical Novels - Lere Adeyemi (Yoruba Studies Review)
The assumption that history posits itself as a fact, while literature is to be taken as an artistic form, only for entertainment (i.e., the difference between truth and falsehood, reality and illusion) has long been debated by formalists and soclologlsts of literature. In Yoruba society, literature and history are important in explaining the fullness of life and the world around us. It is against this background that this paper examines the relationship between literature and history and how Yoruba novelists use their works as vehicles for the representation of history. We adopt the theory of New Historicism to analyze T.A.A. Ladele's lgbi Aye n yi and Olu Owolabi's Ote Nibo. Some of the findings reveal that: both Yoruba literature and history are closely related, they are both based on Yoruba experience and Yoruba existence either in the past or present; while Ladele Interprets the history of the dignity and royal glamour of the Yoruba oba in the precolonial era as a form of domination which is often achieved through culturally-orchestrated consent rather than force; Owolabi represents the hlstory of party politics in Yoruba society as fraudulent, deceltful, full of bitterness and violence. The paper concludes that both novelists are subjective in their representation of Yoruba history, but they successfully establfsh the fact that the novel is a repository of history; however, such history is not a mere chronlcle of facts and events, but rather a complex description of human reality and a challenge to the preconceived notions of the societies from which they emerged.